Nutritional Status of Under-Five Children in Western Nepal - Shrestha, Bandana (Journal of Nepal Paediatric Society, 2014)
Introduction: Undernutrition is a major health problem in developing countries which may have adverse effects on growth and development of an individual. The objectives of this study were to assess the prevalence and grades of malnutrition in children below 60 months of age, attending outpatient department at Gandaki Medical College teaching hospital. Materials and Methods: A prospective study was conducted among 556 children below 60 months of age from August to December 2013. Weight and length/height were measured using standard technique and were plotted on WHO centiles curves and severity determined based on WHO classification. The prevalence of underweight, stunting and wasting were determined by anthropometry. Results: Based on WHO classification, out of 556 children, 20.2% were underweight, 34% were stunted and 15.1% were wasted respectively. Of them, severe underweight were 4.7%, severe stunted were 14.1% and severe wasted were 7.2% respectively. Conclusion: A high prevalence of undernutrition exists in under- five children attending a tertiary hospital in a western region of Nepal. DOI: http://dx.doi.org/10.3126/jnps.v34i2.10566 J Nepal Paediatr Soc 2014;34(2):119-124